The Influence of Perceived Usefulness, Trust, and Risk on Loyalty in the TikTok Shop: Test of Consumer Satisfaction as a Mediation Variable - Elisabeth Fionna Evania Harianto; Jeanne Ellyawati (Program MM Universitas Surabaya, 2023)
Purpose: This study aims to analyze the effect of perceived usefulness, trust and risk on loyalty with consumer satisfaction as a mediating variable at the TikTok Shop. Method: This study's research method was a questionnaire survey. The population in this study were consumers born in 1997 – 2012 (generation Z) and had used the TikTok Shop ≥ 2 times. The sample in this study was 232 respondents. The sampling technique uses a non-probability sampling technique with a purposive sampling approach with an analytical tool, namely PLS-SEM (Partial Least Square - Structural Equation Modeling). Results: The results of data analysis with a significance of 0.05 indicate that the effect of perceived usefulness on customer satisfaction and loyalty has no positive effect. The effect of trust on consumer satisfaction has a significant effect, but the effect of trust on consumer loyalty does not have a significant effect. The effect of risk on customer satisfaction and loyalty has a significant effect. The influence of consumer satisfaction mediates consumer loyalty.